Apicotomy as Treatment for Failure of Orthodontic Traction. (26th December 2013) - Osório, Leandro Berni; Ferrazzo, Vilmar Antonio; Serpa, Geraldo; Ferrazzo, Kívia Linhares
Abstract : Objective. The purpose of this study was to present a case report that demonstrated primary failure in a tooth traction that was subsequently treated with apicotomy technique. Case Report. A 10-year-old girl had an impacted upper right canine with increased pericoronal space, which was apparent on a radiographic image. The right maxillary sinus showed an opacity suggesting sinusitis. The presumptive diagnosis was dentigerous cyst associated with maxillary sinus infection. The plan for treatment included treatment of the sinus infection and cystic lesion and orthodontic traction of the canine after surgical exposure and bonding of an orthodontic appliance. The surgical procedure, canine position, root dilaceration, and probably apical ankylosis acted in the primary failure of the orthodontic traction. Surgical apical cut of the displaced teeth was performed, and tooth position in the dental arch was possible, with a positive response to the pulp vitality test. Conclusion. Apicotomy is an effective technique to treat severe canine displacement and primary orthodontic traction failure of palatally displaced canines.